1999
DOI: 10.1159/000018702
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects on the Regulation of Pancreatic Secretion after Gastric Surgery

Abstract: Background: Apart from smoking, known risk factors for the development of pancreatic carcinoma are few, gastric resection being proposed as one. The trophic effect of cholecystokinin (CCK) on the pancreatic gland is well known from animal experience and increased concentrations of CCK in plasma have been shown to induce pancreatic neoplasia experimentally. In several studies the release of CCK in response to food ingestion has been shown to be increased following gastric surgery. However, in those studies, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2000
2000
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Tobacco smoking, diabetes mellitus, cholelithiasis, and pancreatitis increase the risk of pancreatic cancer (92). Hedberg and colleagues (93) found that a disturbed regulation of pancreatic enzyme secretion, or a regulatory dysfunction of the pancreatic gland, could contribute to the development of pancreatic carcinoma in patients after partial gastrectomy. Their studies suggest that the hormone CCK, which was shown to induce experimental neoplasia, is not involved in this phenomenon.…”
Section: Metabolism Of Nicotine and Its Effects On The Structural Andmentioning
confidence: 99%
“…Tobacco smoking, diabetes mellitus, cholelithiasis, and pancreatitis increase the risk of pancreatic cancer (92). Hedberg and colleagues (93) found that a disturbed regulation of pancreatic enzyme secretion, or a regulatory dysfunction of the pancreatic gland, could contribute to the development of pancreatic carcinoma in patients after partial gastrectomy. Their studies suggest that the hormone CCK, which was shown to induce experimental neoplasia, is not involved in this phenomenon.…”
Section: Metabolism Of Nicotine and Its Effects On The Structural Andmentioning
confidence: 99%
“…Die Gastringesamtsekretion nach Stimulation ist um 43% niedriger als bei nichtoperierten Kontrollpatienten [9]. In einer klinischen Studie von Hedberg et al [33] findet sich auch 8 Jahre nach Billroth-II-Resektion kein Gastrinanstieg im Nahrungsstimulationstest [33]. Die erniedrigten Gastrinkonzentrationen nach Gastrektomie erlangen mo È glicherweise auch klinische Bedeutung bei der Entstehung der exokrinen Pankreasinsuffizienz nach Gastrektomie [34].…”
Section: Gastrinunclassified